(untitled) (Hiroshima, Japan, 1990)
Contemporary Japanese feel the presence of the divine - the invisible realm of the anima - in every part of the creative process. Images of some aesthetics in life.
Keywords: Mỹ học, Nhật Bản,Aesthetics, Japanese